2013
DOI: 10.1177/0278364913489205
|View full text |Cite
|
Sign up to set email alerts
|

Towards dynamic trot gait locomotion: Design, control, and experiments with Cheetah-cub, a compliant quadruped robot

Abstract: We present the design of a novel compliant quadruped robot: Cheetahcub, and a series of locomotion experiments with fast trotting gaits. The robot's leg configuration is based on a spring-loaded, pantograph mechanism with multiple segments. A dedicated open loop locomotion controller was derived and implemented. Experiments were run in simulation and in hardware on flat terrain and with a step-down, demonstrating the robot's self-stabilizing properties. The robot reached a running trot with short flight phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
265
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(283 citation statements)
references
References 66 publications
6
265
0
4
Order By: Relevance
“…RC Fig. 4 The compliant quadruped robot used for experimentation (rendered image), developed at Biorobotics laboratory, EPFL, Switzerland (Spröwitz et al, 2012). Snapshots of the real robot during walking and trotting are provided in Fig.…”
Section: The Experimental Compliant Quadruped Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…RC Fig. 4 The compliant quadruped robot used for experimentation (rendered image), developed at Biorobotics laboratory, EPFL, Switzerland (Spröwitz et al, 2012). Snapshots of the real robot during walking and trotting are provided in Fig.…”
Section: The Experimental Compliant Quadruped Robotmentioning
confidence: 99%
“…In Section 2 the kMPs extracted from walking, trotting, and galloping are analyzed. The compliant quadruped robot (Spröwitz et al, 2012) that was used to test the horse-like trajectories synthesized is introduced in Section 3. Next, in Section 4, the method used to generate these trajectories by reconstruction from kMPs is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Works have been carried out in the field in recent years, such as LittleDog (Kolter and Ng, 2011), BigDog (Raibert et al, 2008), HyQ (Boaventura et al, 2013), Tekken (Fukuoka et al, 2003), Cheetahcub (Spröwitz et al, 2013), LS3 (Bloss, 2012) [7], Baby Elephant , MIT Cheetah (Hyun et al, 2014) and so on. Conventionally, trunks of quadruped robots are all designed as a single rigid body or with a passive compliant joint.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the previous research for this class of small compliant quadrupedal robots showed interest in slow but robust movement over very rough terrain, using techniques to find optimal foot placement [6]. Other research focussed on running in a bounding gait [8], [9], and more recently, trotting gaits have been developed for small compliant robots as well, e.g., for the Reservoir Dog [10] and the Cheetah-cub robot [11], two direct predecessors of the Oncilla. The purpose of our research on the Oncilla is to continue this trend, but with more and improved actuators that enable us to develop faster movement and dynamical gaits, as well as more realistic turning behaviors.…”
Section: Introductionmentioning
confidence: 99%